Does practicing good governance enhance the public trust towards the Lebanese Government? - Alaaraj, Hassan; Ibrahim, Fatimah Wati (IJSRP.ORG, 2014)
The objective of this paper is to examine empirically the influence of good governance practices on the public trust in Lebanon.It presents a theoretical research framework to understand this relationship supported by literature review from recent studies. A survey was conducted among SMEs in the capital Beirut, where 400 questionnaires were distributed among managers and employees resulting 94 percent usable response rate.The research hypothesis was accepted through analyzing the data by SPSS and SEM.The main findings indicate that good governance practices have a positive and significant influence on public trust in Lebanon (p<0.001). Future studies are recommended to extend the empirical research in terms of good governance practices and more specifically at the level of sample and geographical distribution.